Comprehensive test of ultra-efficient air conditioner with smart evaporative cooling ventilation and photovoltaic. (15th February 2022) - Yang, Zixu; Zhang, Youlin; Xiao, Hansong; Zhuang, Rong; Liang, Xiangfei; Cui, Mengdi; Li, Xin; Zhao, Jiaan; Yuan, Qi; Yang, Ruiqi; Wang, Baolong; Shi, Wenxing
Highlights: An air conditioner with evaporative cooling fresh air and photovoltaic is proposed. The gas-injected vapor compression cycle with relay cooling was applied. Strategies of ventilation, water use, and indoor environment control were proposed. The calculated comprehensive electricity-saving rate was 84.1%. The test seasonal performance reached 8.43 kWh/kWh, an improvement of 140.7%. Abstract: Going by current usage trends, the use of room air conditioners will increase by three times by 2050. Therefore, it is necessary to investigate an ultra-efficient air conditioner with extremely low operating energy consumption to realize the goal of climate change, especially in the (sub) tropical area. In this paper, an ultra-efficient air conditioner with smart evaporative cooling ventilation and photovoltaic is proposed, which is composed of a highly efficient air conditioner, a fresh air ventilator with evaporative cooling, an evaporative condenser, and a photovoltaic. The mechanical vapor compression system adopts a gas-injected vapor compression cycle with relay cooling, which adapts to extremely high temperatures and harsh environments. Fresh air ventilation, water usage, and indoor temperature/humidity control strategies are also proposed. In the 31-day field test, the independent ventilator operation hours accounted for approximately 38.4% of the total test period. The electricity savings reached 89.8% as the indoor temperature and humidity satisfied all requirements. Through a typical 10-day lab-simulated year-round performance test, the calculated annual power consumption of the ultra-efficient air conditioner was 746.2 kWh, which was 82.8% lower than that of the baseline prototype. Based on the Indian Seasonal Energy Efficiency Ratio test, the calculated results revealed a consumption of 8.43 kWh/kWh, an improvement of approximately 140.7%. The comprehensive electricity-saving rate was 84.1%. The developed prototype won the global cooling prize since it will counterbalance the booming of residential cooling demand in the future, demonstrating a reliable route for energy savings for room air conditioners.